Odpowiedzi

2010-01-05T23:10:30+01:00
A)5x+y=7
y=7-5x

b)3y-x=3
3y-3=x

c)3x=y-5
y- 3x +5

d)2y=x+12
y= 0,5x +6

e)25x+5y=10
y=2-5x

f)3x-9y=6
x- 3y=6
x= 6 +3y

g)4x+2y=8
2y=8-4x
y=4-2x

h)2(x+y)=6
2x+2y=6
x= 3-y

i)3(x+1)=2(4-y)
3x+3 = 8 - 2y
3x=8-2y-3
x=1/3(8-2y-3)
3 4 3
2010-01-05T23:11:57+01:00
A)y=7-5x
b)-x=3-3y/×(-1)
x=-3+3y
c)y=3x+5
d)x=2y-12
e)25x+5y=10/:5
5x+y=2
y=2-5x
f)3x-9y=6/:3
x-3y=2
x=2+3y
g)4x+2y=8/:2
2x+y=4
y=4-2x
h)2(x+y)=6
2x+2y=6/:2
x+y=3
x=3-y
i)3(x+1)=2(4-y)
3x+3=8-2y
3x-5=2y/:2
1½x-2,5=y